Nonclassical Monocytes (CD14dimCD16+) Are Associated With Carotid Intima-Media Thickness Progression for Men but Not Women: The Multi-Ethnic Study of Atherosclerosis—Brief Report. Issue 5 (25th March 2021) - Feinstein, Matthew J.; Doyle, Margaret F.; Stein, James H.; Sitlani, Colleen M.; Fohner, Alison E.; Huber, Sally A.; Landay, Alan L.; Heckbert, Susan R.; Rice, Kenneth; Kronmal, Richard A.; Hedrick, Catherine; Manichaikul, Ani; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Few studies of population-based cohorts have investigated prospective associations of lymphoid and myeloid cell subsets in cardiovascular disease onset and progression. The purpose of this analysis was to determine associations of prespecified myeloid and lymphoid lineage cell subsets with common carotid artery intima-media thickness (IMT) progression. Approach and Results: We performed a prospective case-cohort study of 1195 participants from the Multi-Ethnic Study of Atherosclerosis who had peripheral blood mononuclear cells stored from the baseline examination. Key exposure variables were prespecified subsets of lymphoid and myeloid lineage immune cells, phenotyped by multicolor flow cytometry. The primary outcome was progression from baseline (Exam 1) to year 10 (Exam 5) in common carotid IMT. Higher proportions of nonclassical monocytes (CD14dimCD16++) were significantly associated with IMT progression over 10 years, but classical monocytes (CD14++CD16−), CD4+CD28− T cells, and T helper cells producing IL-17 (interleukin 17; T helper 17 cells) were not associated with significant changes in IMT over 10 years. There were significant interactions between monocyte subsets and sex with respect to IMT progression: in sex-stratified analyses, nonclassical monocytes were associated with significant IMT progression and classical monocytes were associated with significant IMT regression for men, whereas there were no significant associations of monocyte subsets with IMT change for women. Conclusions: Nonclassical monocytes were associated with progression of carotid IMT. There were significant sex differences in associations of monocyte subsets with IMT progression: for men, nonclassical monocytes were associated with IMT progression and classical monocytes were associated with regression, whereas these associations were null for women.